ON THE EFFECTIVENESS OF A PREOPERATIVE PRE-HOSPITAL ADMISSION IN PATIENTS UNDERGOING EXTRACORPOREAL HEART SURGERY - . Morales, J. C; . Renones, B; Ortega, M. (Cuestiones de Fisioterapia, 1999)
It has studied if hospital preadmission preoperatory (PP) doing improve colaboration in postoperatory of patients subjected to extracorporeal cardiac surgery. Two groups of patients were done, one group made the physiotherapy preoperatory before hospital admission, developing it at home, and another group made it at the moment of admission. The collaboration grade was valuated in preoperatory of the first group and in the post operatory of both groups, through a relation between number of times a day that patient made exercises divided by total number of days. The collaboration grade in post operatory was greater in the group which made PP, but there are not significative differences with the other group. Age of patients and the type of cardiac pathology have not affected in the post operatory collaboration grade. There is a positive correlation between collaboration of preoperatory and post operatory.